Fabrication And Characterization Of Polyvinyl Alcohol Asymmetric Membrane Supported By Polyvinylidene Fluoride For Dehydration Of Ethanol Via Pervaporation - Tan, Chee Yeang (Universiti Sains Malaysia, 2017)
The asymmetric PVA-MWCNT/PVDF/Non-woven membrane is fabricated for dehydration of 95 wt. % aqueous ethanol solution at 30 °C via pervaporation. The functionalized MWCNT containing carboxyl groups (-COOH) functional groups are incorporated in the PVA membrane as hydrophilic nanofillers to enhance the permeate flux and separation factor by increasing the solubility and diffusivity between water molecules and the pervaporation membrane. Besides, the porous PVDF layer is employed as the support layer for the PVA membrane, to increase the mechanical strength of pervaporation membrane. To further enhance the structural integrity of the membrane, the PVA polymer is immobilized into the porous sites of PVDF porous layer via vacuum filtration process. The results obtained from mechanical tensile test showed that the effectiveness of these modifications in improving the mechanical strength. In the presence of functionalized MWCNT, the strain before break of asymmetric PVA-MWCNT/PVDF/Non-woven membrane had reduced approximately 14 % from the values recorded for the asymmetric PVA/PVDF/Non-woven membrane while 18 % increase in tensile stress is observed. For swelling test, 15 % decrease in terms of swelling degree is observed when the asymmetric PVA-MWCNT/PVDF/Non-woven membrane is tested with 95 wt. % aqueous ethanol solution. Besides that, the presence of functionalized MWCNT as filler enhanced the separation factor by 4 folds during dehydration of 95 wt. % aqueous ethanol solution at 30 °C via pervaporation. However, the total flux obtained for the asymmetric PVA-MWCNT/PVDF/Non-woven membrane is only 10 % of the value obtained for the asymmetric PVA/PVDF/Non-woven membrane.